PENGARUH ASIMETRI INFORMASI, MEKANISME CORPORATE GOVERNANCE DAN KOMPENSASI BONUS TERHADAP MANAJEMEN LABA - Yustiningarti, Norma Dwi; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine the influence of asymmetric information, corporate governance mechanism, and bonus compensation to the earnings management. The research population is all consumer goods companies which are listed in Indonesia Stock Exchange in 2013-2015 periods. The sample selection has been conducted by using purposive sampling method, and it has obtained as many as 63 observation. The statistic method has been carried out by using multiple regressions analysis. In this research, asymmetric information has been measured by using relative bid-ask spread, corporate governance mechanism has been measured by using factor score, and bonus compensation has been measured by using dummy which gives value 1 to companies that give bonuses and 0 for companies that do not give a bonus. Earning management has been measured by using modified jones model. The result of the research shows that simultaneously the asymmetric information, corporate governance mechanism and bonus compensation has significant influence to the earnings management. The result of partial test shows that asymmetric information has significant influence to the earnings management, bonus compensation has significant and positive influence to the earnings management, and corporate governance mechanism does not have any significant influence to the earnings management.Keywords: Asymmetric information, corporate governance mechanism, bonus compensation, earnings management.